2002
DOI: 10.1021/ja005839t
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Three Isomers of Tm@C82 by 13C NMR Spectroscopy

Abstract: The (13)C NMR spectra were measured for three isomers of Tm@C(82), which is one of the divalent metallofullerenes. The molecular symmetries were determined for each isomer: isomer I has C(s) symmetry, isomer II has C(2) symmetry, and isomer III has C(2v) symmetry. Moreover the cage structure of Tm@C(82)(III) was found to be C(82)(9). As a result, it was revealed that Tm@C(82)(III) has a cage identical to that of La@C(82), which is one of the trivalent metallofullerenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 12 publications
6
59
1
Order By: Relevance
“…Similar effects were observed in numerous 13 C NMR studies on Ce‐based mono‐ and dimetallofullerenes and their derivatives 23. To our knowledge, the only paramagnetic 13 C NMR studies of non‐Ce lanthanide metallofullerenes were reported for three isomers of Tm@C 82 24 and for the Pr@C 82 − anion 25. The influence of multiple 4f electrons on the carbon cage is still an unresolved question which requires further study.…”
Section: Resultsmentioning
confidence: 97%
“…Similar effects were observed in numerous 13 C NMR studies on Ce‐based mono‐ and dimetallofullerenes and their derivatives 23. To our knowledge, the only paramagnetic 13 C NMR studies of non‐Ce lanthanide metallofullerenes were reported for three isomers of Tm@C 82 24 and for the Pr@C 82 − anion 25. The influence of multiple 4f electrons on the carbon cage is still an unresolved question which requires further study.…”
Section: Resultsmentioning
confidence: 97%
“…Compounds containing Tm 2+ are now known for organometallic complexes36,37,38 and also for endohedral fullerenes 39. As an example of the latter, the three isomers of Tm@C 82 have been formulated with the electronic distribution, Tm 2+ [C 82 ] 2− 40,41. For Tm@ C 3v -C 94, the use of the same C 3v -C 94 cage structure as found for the calcium compound suggests that the Tm 2+ [C 94 ] 2− electronic distribution is probable.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular symmetries of Tm@C 82 (B, A, C) were determined as C s , C 2 , and C 2v , respectively, by using NMR spectroscopy. [16] Therefore, one can deduce that the symmetries of Yb@C 82 (I, II, III) should be C s , C 2 , and C 2v , respectively. In our earlier report, the UV/Vis/near-IR absorption spectra of Yb@C 82 (I, II, III) were given, which were very similar to those of Tm@C 82 (B, A, C).…”
Section: Introductionmentioning
confidence: 98%